Full-scale evaluation of methane production under oxic conditions in a mesotrophic lake. Issue 1 (December 2017) - Donis, D.; Flury, S.; Stöckli, A.; Spangenberg, J.; Vachon, D.; McGinnis, D.
Abstract Oxic lake surface waters are frequently oversaturated with methane (CH4 ). The contribution to the global CH4 cycle is significant, thus leading to an increasing number of studies and stimulating debates. Here we show, using a mass balance, on a temperate, mesotrophic lake, that ~90% of CH4 emissions to the atmosphere is due to CH4 produced within the oxic surface mixed layer (SML) during the stratified period, while the often observed CH4 maximum at the thermocline represents only a physically driven accumulation. Negligible surface CH4 oxidation suggests that the produced 110 ± 60 nmol CH4  L−1  d−1 efficiently escapes to the atmosphere. Stable carbon isotope ratios indicate that CH4 in the SML is distinct from sedimentary CH4 production, suggesting alternative pathways and precursors. Our approach reveals CH4 production in the epilimnion that is currently overlooked, and that research on possible mechanisms behind the methane paradox should additionally focus on the lake surface layer. The contribution of methane (CH4) produced in oxic freshwaters to the global atmospheric CH4 budget is poorly constrained. Here, using a mass balance and in-situ incubations, the authors show that significant CH4 emissions are supported by CH4 produced in the oxic surface mixed layer in Lake Hallwil.